Co-operative housing : proceedings of a seminar held at Fremantle, WA on 29th April, 1992 by Australian Institute of Urban Studies, the Office of the Family. (Australian Institute of Urban Studies, Western Australian Division, 1992)
Takes a new look at cooperative housing through ideas presented by professionals, residents, government and business representatives.